Korelasi Antara Kebiasaan Belajar dengan Hasil Belajar Siswa pada Mata Pelajaran Akidah Akhlak Kelas VII B Ddi Madrasah Tsanawiyah Hidayatul Mubtadiin Sidoharjo Kecamatan Jati Agung Kabupaten Lampung Selatan Tahun Ajaran 2024/2025: Penelitian - Lailatul Khusna; A. Habib; Sri Rahayuningsih (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine the correlation between study habits and students' learning outcomes in the subject of Aqidah Akhlaq for class VII B at Madrasah Tsanawiyah Hidayatul Mubtadiin Sidoharjo, Jati Agung District, South Lampung Regency, for the 2024/2025 academic year. This research uses a quantitative approach with a correlational method. Data collection techniques were carried out through questionnaires to measure students' study habits, documentation of their Aqidah Akhlaq learning outcomes, and interviews and observations as supporting data. The respondents in this study consisted of 30 students. The results of the study indicate that most students have study habits that fall into the medium to high category, including habits such as reviewing lessons, taking notes, studying regularly at home, and being prepared for exams. Meanwhile, students' learning outcomes in Aqidah Akhlaq varied, but in general, they were in the fairly good category. Based on data analysis using the Pearson Product Moment correlation formula, a correlation coefficient value of 0.61 was obtained, indicating a moderately strong positive relationship between study habits and students’ learning outcomes. The significance value shows that the relationship is statistically significant, meaning that good study habits make a real contribution to improving students’ academic performance. Therefore, it can be concluded that there is a significant correlation between study habits and students' learning outcomes in the Aqidah Akhlaq subject. This finding emphasizes that fostering positive study habits, such as effective time management, independent comprehension, and consistency in learning, is essential to be instilled early to support students’ academic achievement, especially in religious education. Hence, teachers, parents, and the school environment need to work in synergy to guide and facilitate students in building effective and sustainable learning patterns.